Developmental changes in cell wall polysaccharides from sweet cherry (Prunus avium L.) cultivars with contrasting firmness - Salato, Gloria Silvia (2013)
Firmness is a major quality attribute of fresh cherries, and is also a main factor affecting susceptibility to bruising andpostharvest rots.Inorder to identify the factorsdetermining the texturaldifferences between genotypes, we evaluated the solubilization, depolymerization and monosaccharide composition of pectin and hemicelluloses from two cultivars with contrasting firmness (‘Sweetheart’, firm and ‘Newstar’, soft) at four different developmental stages. Firm ‘Sweetheart’ cherries had higher contents of cell wall material than soft ‘Newstar’ fruit. Moderate depolymerization of hemicellulose and tightly bound pectins was detected irrespective of cultivar firmness. The general pattern and extent of uronic acid solubilization was quite similar in both cultivars. Rhamnogalacturonan I (RG-I) seemed to be preferentially solubilized in firm ‘Sweetheart’ fruit as opposed to tightly bound homogalacturonans (HG) in soft cherries. Pectic polymers with higher neutral sugar to uronic acids ratio were found from early development in soft ‘Newstar’ fruit. Overall, soft ‘Newstar’ fruit had reduced wall content and higher branching of tightly bound pectins than firm ‘Sweetheart’ fruit. These factors may be associated with the varietal differences in cherry firmness.